(untitled) (Global Journal of Human-Social Science, 2021)
The purpose of this study was to determine the best model in predicting ihsan behavior, especially during the Covid 19 pandemic as it is currently from eight ihsan character: ambitious, certain/confident, courageous, hard-working, enthusiastic, patient and persistent, generous, and grateful. The method of research was survey and 215 students at As Syafi’iyah Islamic University were selected as the sample. The results revealed that: a) only three out of eight qualities that significantly influenced the development of ihsan behavior, namely ambitious, patient & persistent, and generous; b) the qualities of ambitious, patient & persistent, and generous simultaneously contributed to shaping ihsan behavior by 58.5%; c) the best mathematical model to predict ihsan behavior was Y=-0.465+0.211X1+0.413X2+0.453X3 (X1=ambitious; X2=patient & persistent; X3=generous); d) being generous served as the quality with the highest sensitivity of the effect on ihsan behavior (always do the good deeds) development, followed by patient & persistent and ambitious.